Bernardi Guidonis scripta de Sancto Dominico (Book Review). - Mulchaney, M. Michele (Speculum, 2001)
Reviews the book 'Bernardi Guidonis scripta de Sancto Dominico,' by Bernardus Guidonis and edited by Simon Tugwell.